Association of Serotonin 1 A Receptor(5-HT1A) (rs6296G/C) Gene Polymorphism and Serotonin Levels in Patients with Psychological Stress (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Stress has been linked to a number of psychological conditions, including major depressive disorder, schizophrenia, and Alzheimer's disease (AD). Serum serotonin levels and serotonin receptor gene polymorphism were thought to be linked to psychological stress-related illness symptoms.Materials and Methods: In this study, 60 male patients with psychological stress were divided into 20 groups: those with Alzheimer's, schizophrenia, and major depression. Thirty-nine individuals were included as a healthy group. Serum serotonin levels were measured by ELISA, and the results were correlated with the serotonin 1 A receptor (5-HT1A) (rs6296G/C) gene polymorphism.    Results: The findings indicated a statistically significant (p≤0.05) reduction in serotonin levels across all patient groups when compared to the healthy group. Additionally, the serotonin receptor (rs6296G/C) gene polymorphism results demonstrated that the majority of patients with Alzheimer's and schizophrenia had the highest percentage (50%) of 5-HT1A genotype GC when compared to the healthy group.                                                                                  Conclusion: It was determined that serotonin levels and 5-HT1A gene polymorphism are related in psychological stress disorders, such as depression, schizophrenia, and Alzheimer's disease.